2023
DOI: 10.1021/acsami.3c00140
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Nitric Oxide-Releasing Ampicillin as a Potential Strategy for Combatting Bacterial Biofilm Formation

Abstract: Biofilm formation on biomaterial interfaces and the development of antibiotic-resistant bacteria have decreased the effectiveness of traditional antibiotic treatment of infections. In this project, ampicillin, a commonly used antibiotic, was conjugated with S-nitroso-N-acetylpenicillamine (SNAP), an S-nitrosothiol compound (RSNO) used for controlled nitric oxide (NO) release. This novel multifunctional molecule is the first of its kind to provide combined antibiotic and NO treatment of infectious pathogens. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Conjugation of the NO donor compound S -nitroso- N -acetyl- d -penicillamine (SNAP) to ampicillin was achieved following a previous report with minor deviation. 16 First, a thiolactone derivative (NAPTH) of the acetylated penicillamine (NAP) precursor to SNAP was prepared following previous reports with slight modification. 17,18 In brief, NAP was dissolved in chilled anhydrous pyridine (250 mg mL −1 ) with chilled acetic anhydride (∼3.5 molar equivalent to NAP) added dropwise.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conjugation of the NO donor compound S -nitroso- N -acetyl- d -penicillamine (SNAP) to ampicillin was achieved following a previous report with minor deviation. 16 First, a thiolactone derivative (NAPTH) of the acetylated penicillamine (NAP) precursor to SNAP was prepared following previous reports with slight modification. 17,18 In brief, NAP was dissolved in chilled anhydrous pyridine (250 mg mL −1 ) with chilled acetic anhydride (∼3.5 molar equivalent to NAP) added dropwise.…”
Section: Methodsmentioning
confidence: 99%
“…These results corroborate our prior characterization. 16 SNAPicillin purity was confirmed via NMR and a product of >90% purity was used for further studies.…”
Section: Methodsmentioning
confidence: 99%
“…To detect the NO release under the physiological environment, we placed RSNO, SNO-CS and SNO-CS@MoS 2 in PBS under natural light at 37 ℃. The results showed that the NO release from the three groups was basically the same, indicating that the slow release of RSNO was mainly related to natural light and room temperature [ 50 , 51 ] (Fig. S8 ).…”
Section: Methodsmentioning
confidence: 99%
“…NO is a naturally existing molecule that plays a crucial role in numerous physiological processes. Recent research suggests that the administration of NO at appropriate concentrations can effectively address various human disorders. , The doses of exogenous NO have been observed to strongly inhibit bacterial growth or directly eliminate it. , Gram-positive (Staphylococcus aureus and Staphylococcus epidermidis) and Gram-negative bacteria (Pseudomonas aeruginosa and Escherichia coli), including methicillin-resistant strains of S. aureus, are susceptible to NO broad-spectrum antibacterial action.…”
Section: Introductionmentioning
confidence: 99%